Konsep Al-Birr Menurut Tafsir An-Nur Karya Hasbi Ash-Shiddieqy - Nugraha, Aliffian Cahya; Amrulloh, Muhamad; Wirastho, Edy (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
This research examines the concept of al-Birr according to Tafsir An-Nur by Hasbi Ash-Shiddieqy and its implementation in contemporary life. The Qur'an describes humans as creatures created with the best forms and abilities, and in their social interactions, humans are ordered to help each other in virtue and piety as stated in Surah Al-Maidah verse 2. This research uses a descriptive qualitative method with a literature approach, where the main data comes from Tafsir An-Nur and other supporting sources from books, journals, and related documents. The results show that al-Birr in Hasbi Ash-Shiddieqy's view includes two main aspects: aspects of faith and belief, as well as aspects of charity and deeds. The aspect of faith includes belief in Allah, the last day, angels, books, and prophets, while the aspect of charity includes the implementation of worship such as prayer and zakat, as well as social virtues such as providing assistance to the needy and being kind to others. The implementation of the concept of al-Birr in modern life emphasises the consistency of faith, the implementation of worship with solemnity, and sincere intentions in charity. True virtue according to the Qur'an and Hasbi Ash-Shiddieqy's interpretation is done without seeking popularity or human praise. This research reveals that the relevance of al-Birr in today's life is as a practical guide to living a better and meaningful life, and avoiding phenomena that eliminate the values of piety such as riya' and showing off.